Dualisme Kewenangan dalam Pengawasan Lembaga Keuangan Mikro Syariah di Indonesia - Fata, Ikmal; Diana, Isna; Pratama, Aditya Ilham; Hasibuan, Taufiq Hidayat; Alfariki, Sofyan Wegi (Prodi Tata Negara (Siyasah) IAIN Langsa, 2024)
The dualism of authority in supervising Sharia Microfinance Institutions (LKMS) in Indonesia creates legal uncertainty and weak oversight. Kemenkop UKM and OJK have different perceptions regarding the regulation of LKMS, leading to overlapping authority. This situation has the potential to hinder the development of LKMS and reduce public trust in the Sharia financial system. LKMS, such as Baitul Maal wat Tamwil (BMT), play a strategic role in empowering the community's economy and promoting Sharia financial inclusion. However, the regulation and supervision of these institutions often overlap due to differing perceptions of authority. Kemenkop UKM considers BMT to be part of a cooperative under its supervision, while OJK views BMT as a financial entity requiring more technical oversight related to financial services. This study employs a legal-normative method with a descriptive analysis approach, examining documents such as books, legislation, and other relevant materials. The findings indicate that this overlap in authority results in legal uncertainty, weak supervision, and potential risks for customers. The impacts include unclear legal protection for consumers, risks of authority misuse, and low compliance with Sharia financial regulations. Furthermore, this condition may hinder the growth of LKMS, reduce public confidence, and slow down efforts to enhance Sharia financial inclusion. Harmonizing regulations and establishing coordination mechanisms between Kemenkop UKM and OJK are essential to strengthening supervision and ensuring the sustainability of LKMS. Regulatory harmonization is crucial in promoting better governance and increasing public trust in Indonesia's Sharia microfinance system.